Neurogenesis-Promoting Natural Product α-Asarone Modulates Morphological Dynamics of Activated Microglia - Cai, Qing; Li, Yuanyuan; Mao, Jianxin; Pei, Gang (Frontiers in Cellular Neuroscience, 2016)
α-Asarone is an active constituent of Acori Tatarinowii, one of the widely used traditional Chinese Medicine to treat cognitive defect, and recently is shown to promote neurogenesis. Here, we demonstrated that low level (3µM) of α-asarone attenuated LPS-induced BV2 cell bipolar elongated morphological change, with no significant effect on the LPS-induced pro-inflammatory cytokine expressions. In addition, time-lapse analysis also revealed that α-asarone modulated LPS-induced BV2 morphological dynamics. Consistently a significant reduction in the LPS-induced Monocyte Chemoattractant Protein (MCP-1) mRNA and protein levels was also detected along with the morphological change. Mechanistic study showed that the attenuation effect to the LPS-resulted morphological modulation was also detected in the presence of MCP-1 antibodies or a CCR2 antagonist. This result has also been confirmed in primary cultured microglia. The in vivo investigation provided further evidence that α-asarone reduced the proportion of activated microglia, and reduced microglial tip number and maintained the velocity. Our study thus reveals α-asarone effectively modulates microglial morphological dynamics, and implies this effect of α-asarone may functionally relate to its influence on neurogenesis.